The Role of Interactive Videos on Children's Motivation in Memorizing Short Letters Aged 4-5 Years at BA Aisyiyah Dukuh - Islami, Anisa Nur; Slamet, Sri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to examine the use of interactive video media as a strategy to motivate children aged 4–5 years in memorizing short Qur'anic surahs. It focuses on how interactive elements such as text, images, audio, and user interaction can increase children’s enthusiasm and support the effectiveness of the memorization process. Methodology: The use of interactive video media created a more engaging and conducive learning atmosphere for children. The combination of multimedia elements captured the children's attention, helped them stay focused, and reduced boredom during memorization activities. As a result, the children were more motivated and receptive to memorizing short surahs. Applications/Originality/Value: This study highlights the effectiveness of interactive video as a tool for improving early childhood Qur'an memorization. It offers practical insights for educators and parents in selecting appropriate media to support young learners. The findings emphasize the importance of balancing digital media use with direct personal interaction to optimize both motivation and learning outcomes in early childhood religious education.